An assessment of the impact of food aid programs to household food security in Zimbabwe : a case of Chimanimani District - Matongo, Callister Wish (Midlands State University, 2020)
This study was carried out in Chimanimani district and it seeks to understand the impact of food aid on household food security. The study sampled 40 households using convenient sampling who are the beneficiaries and non-beneficiaries of food aid. Food aid program is widely debated in the world and has made many people to believe that food aid has a disincentive effect while others believe it is an essential tool for agriculture and food security development. For the past decade, food aid deliveries have featured Chimanimani district following its food deficit. This research utilized both qualitative and qualitative research designs. It made use of focus group discussions with local authorities of Chimanimani district, local traditional leaders, government field workers and villagers as well as questionnaire interviews with individuals while observations became an integral part. A two stage sampling design was chosen in order to systematically sample the wards and then randomly sample individuals from those wards. A lot of secondary information was also obtained mostly ZimVAC rural vulnerability assessments. The study found out that negative dependency on food aid occur when rigorous assessments are not done prior to implementation, it does not target the most vulnerable thereby including undeserving cases and excluding deserving cases, it is implemented at the wrong time and if the quantities given are more than the requirements. It is concluded that the food aid programs which were implemented in the area were designed properly such that it did not encourage negative dependency. However, it fell short of attaining the objective of promoting or strengthening livelihoods. In order to attain the objective of food security for the local people of Chimanimani West it is recommended that both the public and private sectors revamp and expand the irrigation developments in the region. Drought resistant crops such as millet and sorghum should be promoted. New farming technology of conservation farming is highly recommended to improve on crop yields. Finally it is recommended that food aid be combined with input support as a way of directly promoting production